Componentes de inteligencia de negocios en el Área de la Energía, las Industrias y los Recursos Naturales no Renovables. - Tuza Cuenca, Edgar iván (2016)
Information has become a necessary element for the emergence of modern business, you need to have knowledge about their competitors and the market in which they operate, as such historical data becomes a source of valuable information to be treated appropriately increase the competitiveness of any organization. Institutions of higher education can also make use of large amounts of information from different areas or departments and their careers, this information can be useful for potential weaknesses in academic performance. The present investigation project describes a process aimed at incorporating components of business intelligence (BI) in the Area of Energy, Process Industries and non-renewable National University of Loja Natural Resources. So, it will build a Data Warehouse focused on the academic side of it. The Data Warehouse area will consist of two Data Marts (student-teacher), for construction activities such as performed: obtaining business requirements (identification of questions), identifying perspectives of analysis and performance indicators, analysis of the information contained within SGAWebServices which is the main OLTP development of this project and the development of a relational model that will act as temporary storage, and based on the latter populate dimensional models (Data Marts), based on the star schema and following Ralph Kimball’s architecture. The implementation and integration of Data Marts was performed by processes Extraction, Transformation and Loading (ETL) from data contained in the SGAWebServices of the National University of Loja, the same that will be taken to a temporary storage called STAGE_ENERGIA, then be brought to each Data Mart, and finally show the user the information required by tools Online Analytical Processing (OLAP), and complemented with additional reporting tools, based on the data contents in each Data Mart.